Exploring Digital Personal Branding Practices Through Linkedin Among Marketing Undergraduates: Evidence From The University Of Jaffna - Pushpakumara, P.P.M.M.; Mendis, T.N.; Dilogini, S. (Asia Chartered Institute Of Digital Marketing-(ACIDM), 2026)
Background: In today’s competitive virtual environment, undergraduates must differentiate themselves to secure career opportunities. Although digital personal branding on platforms such as LinkedIn is increasingly recognized as important for professional growth, limited research has examined University of Jaffna undergraduates’ engagement with these practices. This study focuses on marketing undergraduates at the University of Jaffna, contributing insights from a less explored context. Objective: This study aims to examine how marketing students build and develop their digital personal brand exclusively through LinkedIn, identifying the opportunities and challenges involved. Methodology: A qualitative research design was adopted. Data were collected through thirty-two semi-structured interviews with marketing undergraduates at the University of Jaffna and analyzed using thematic analysis to identify common and unique personal branding practices and experiences. Key Findings: The study finds that undergraduates mainly use LinkedIn to build professional reputation, expand networks, and enhance employability. Peer recommendations and awareness of specializations were more effective in building trust than overall online visibility. However, challenges remain, including a stronger preference for Facebook over LinkedIn, difficulty in maintaining consistent updates, privacy concerns, and balancing professionalism with prevailing social stigma. Conclusion/Implication: The qualitative findings provide initial insights into digital personal branding in Sri Lankan higher education and highlight the need for systematic institutional support in teaching personal branding. The implications for teachers, students, and institutions show how digital presence can be better utilized for professional advancement.
Keywords: Digital marketing; LinkedIn; Marketing undergraduates; Online presence; Personal branding; Sri Lanka